2011
DOI: 10.1371/journal.pgen.1002147
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Dynamics in Hepatocarcinogenesis: a Comparative Proteomics Study of PDGFC Transgenic and Pten Null Mouse Models

Abstract: We are reporting qualitative and quantitative changes of the extracellular matrix (ECM) and associated receptor proteomes, occurring during the transition from liver fibrosis and steatohepatitis to hepatocellular carcinoma (HCC). We compared two mouse models relevant to human HCC: PDGFC transgenic (Tg) and Pten null mice, models of disease progression from fibrosis and steatohepatitis to HCC. Using mass spectrometry, we identified in the liver of both models proteins for 26 collagen-encoding genes, providing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 37 publications
4
67
0
Order By: Relevance
“…COL6 upregulation has been reported in various aspects of tumor progression. Malignant cancer cells can also express COL6; this has been reported for the mammary gland (18), the colon (35,36), pancreatic ductal adenocarcinomas (37), and hepatocarcinomas (38). Thus, the source of ETP in the tumor microenvironment may be heterogeneous, with signals cooperatively influencing cancer cell behavior through paracrine and autocrine pathways.…”
Section: Discussionmentioning
confidence: 89%
“…COL6 upregulation has been reported in various aspects of tumor progression. Malignant cancer cells can also express COL6; this has been reported for the mammary gland (18), the colon (35,36), pancreatic ductal adenocarcinomas (37), and hepatocarcinomas (38). Thus, the source of ETP in the tumor microenvironment may be heterogeneous, with signals cooperatively influencing cancer cell behavior through paracrine and autocrine pathways.…”
Section: Discussionmentioning
confidence: 89%
“…These studies indicate that in addition to an increase in total collagen in IPF (150,151) there is also a shift toward the less elastic type I collagen, which contributes to pathophysiological abnormalities in fibrosis (51,125,145). A relative increase in type I collagen production (as well as an increase in total lung collagen content) has also been demonstrated in the lungs of patients with ARDS (87,140) as well as in human fibrotic livers (85).…”
Section: Collagen Structure and Composition In Areas Of Fibrosismentioning
confidence: 93%
“…194 A recent mass spectrometry study of the ECM in two rodent models identified 16 different collagens in the liver, and profiled changes in the abundance of collagens and integrins in tumors compared with healthy livers and precancerous fibrotic livers. 195 Neoepitopes of these proteins may serve as valuable markers of liver ECMR. Promising candidates have been reported, including those derived from type IV collagen, 196,197 type I collagen, 198 type V collagen, 199 and type VI collagen.…”
Section: -178mentioning
confidence: 99%